DEVELOPMENT OF A PJBL-BASED STATIONERY CIVILIZATION BOOK FOR SELF-CONTROL CHARACTER EDUCATION IN CHILDREN : Pengembangan Buku Peradaban Alat Tulis Berbasis PjBL untuk Pendidikan Karakter Kontrol Diri pada Anak - Vincentia Septiana Anugrah Wahyuningrum; Gregorius Ari Nugrahanta (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The focus of this study is on children who have trouble managing their own behavior. This study seeks to establish the improvement of children's self-discipline following the implementation of the Project Based Learning approach through the stationery civilization project. The research methodology utilized is the ADDIE model, which falls under the category of Research and Development (R&D) approaches. This study included ten licensed teachers from different areas to meet analysis requirements. It also included ten validators from expert judgment and five teachers as expert judges. Eight fifth grade students at an elementary school in Nanggulan, Kulon Progo were the participants in this study. Testing techniques, as well as non-testing techniques, were used for the sampling process. The study's findings demonstrate that utilizing the PjBL approach can enhance self-discipline in children, showing a notable distinction (p < 0.05) with a substantial influence level (r = 0.983) equivalent to 96%. The study's effectiveness level falls within the high category N-Gain score 74.246%.